The Danube as a natural obstacle in Romanian army operations - Dubicki, Andrzej; Dubicki, Tadeusz (Armia kontra natura, 2020)
The Danube is a significant natural obstacle. Since ancient times it has been used as a defense barrier, an important element of the defense system. Nevertheless, it often turned out that, despite its vastness, the great river was not a significant barrier to the opponent. Romanians have also benefited from this many times, shifting their troops to the southern shore in the wars of 1878, 1913 and 1916. In the article we present mainly the circumstances and course of crossing the Danube in these cases, together with an assessment of the crossing and its importance for the final conclusion of the campaign.